Intellectual Property as Fiduciary Collateral in Indonesian Banking: Legal Guarantees and Creative Economy Financing - Ulil Albab Junaedi; Rofi Wahanisa; Martitah Martitah (Pandecta Research Law Journal, 2026)
Indonesia recognizes intellectual property rights (IPR) as intangible movable assets that may secure financing, yet banking practice still treats IPR as marginal collateral. This study examines how Indonesian law positions IPR as fiduciary collateral, what legal guarantees protect banks and creative economy actors, and why implementation remains limited after Government Regulation No. 24/2022. Using normative legal research, this article analyzes the Copyright Law, Patent Law, Fiduciary Guarantee Law, Creative Economy Law, Government Regulation No. 24/2022, OJK Regulation No. 40/POJK.03/2019, and the 2025 regulation on intellectual property valuers. The analysis is supported by official creative economy data and comparative case studies from Singapore, the United Kingdom, and the United States. The findings show that copyright and patent rights can be bound through fiduciary security because they are transferable economic rights with asset value. The legal guarantees consist of a notarized fiduciary deed, registration, preference rights, third-party enforceability, and execution rights after default. The main implementation gap lies in valuation, secondary market uncertainty, and the absence of IPR from the collateral categories recognized for bank provisioning under OJK asset-quality rules. The novelty of this article lies in connecting IPR doctrine, fiduciary security, prudential banking regulation, and the new Indonesian framework for registered intellectual property valuers.